Pkm Pelatihan Blended Learning Untuk Meningkatkan Kompetensi Guru di Era Digital - Siti Raihan; Wizerti Ariastuti Saleh; Ratih Utami Ramadhaniati; Saprizal (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Blended learning training for elementary school teachers who are members of the Timbuseng Teacher Working Group (KKG), Pattallassang District, Gowa Regency is motivated by the demands of digital transformation in education in the society 5.0 era as well as the readiness of partner schools that already have adequate supporting facilities and a strong willingness to improve digital competence. The aim of this activity is to improve teacher competence in managing blended learning through the use of Google Classroom, Padlet, Canva, Kahoot!, and Quizizz. The method used is a three-day training and workshop with an experiential learning approach, including preparation, implementation, as well as evaluation and mentoring stages. The results showed a significant increase in teacher competence with an average pre-test score of 46.6 increasing to 87.5 in the post-test, and N-Gain values ranging from 0.58 to 0.71 which are included in the medium to high category. All 25 teachers succeeded in producing outputs in the form of 25 Google Classroom classes, 25 Padlet boards, 25 Canva teaching modules, and 25 Kahoot! and Quizizz interactive quizzes. The implications of this activity are increased teacher confidence in managing blended learning and the formation of a WhatsApp-based teacher learning community. In conclusion, blended learning training is effective in improving teacher competence and plays an important role in supporting schools to transform towards inclusive and equitable education